Tatar literature of the early 20th century through the vision of G. D. Gachev's theory of the accelerated development of literature - Ibragimov, Marsel I.; Zagidullina, Daniya F. (The New Research of Tuva, 2024)
The article addresses the applicability of the concept of “accelerated development” to Tatar literature of the early 20th century. It defines the features of the reception of the theory of accelerated development of literatures by Tatar scholars and literary critics. Through the lens of Gachev's theory of accelerated development, several works by prominent Tatar writers of this period are analyzed, including those by G. Tukay, F. Amirhan, and G. Rakhim.Different modes of accelerated development are identified: functional displacement (illustrated by the poetry of G. Tukay, demonstrating the use of medieval poetic forms in new functions); the “leap” (F. Amirhan's play “Unequal” is analyzed as an example of non-classical drama); and synthesis (the potential of synthetic artistic thinking as a factor of accelerated development is explored through the novella “Idel” by G. Rakhim).The conclusion is drawn that two developmental trends coexisted in Tatar literature of the early 20th century: gradual development on the one hand, and accelerated development on the other. Within the first trend, innovation manifests as the development of the Enlightenment paradigm that had taken shape in the last quarter of the 19th century. The second trend is seen as an “explosion”, a “leap”, leading to the creation of artistic works that “outpaced” their time.
Keywords: accelerated development of literature; Georgy Gachev; Tatar literature; Gabdulla Tukai; Fatih Amirkhan; Gali Rahim; Tatar literary studies